1995
DOI: 10.1007/bf01844824
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation in biopsy specimens of dentin

Abstract: Determination of age at death on the basis of aspartic acid racemization in dentin is one of the most reproducible and accurate methods. In Germany, age estimation by this method has so far generally not been applied to living persons, since the extraction of a tooth exclusively for age estimation when it is not medically indicated is regarded as ethically and legally problematic. The development of a biopsy technique applicable to dentin took place against this background. Testing the technique and analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 28 publications
0
31
1
2
Order By: Relevance
“…The estimation of the individual age of an unknown corpse is a relatively frequent problem in forensic medicine [11] while determination of fetal age can be of significance in illegal abortions. The most reliable methods are measurements of fetal body length and body weight but these parameters are only useful in the examination of intact fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of the individual age of an unknown corpse is a relatively frequent problem in forensic medicine [11] while determination of fetal age can be of significance in illegal abortions. The most reliable methods are measurements of fetal body length and body weight but these parameters are only useful in the examination of intact fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, age determination is not suitable with extensive crown destruction in postmortem examination [110] rather than the extraction of the teeth. Ritz et al [110] suggested another less invasive way of racemization estimation by dentinal biopsy specimens taken from molars in living subjects. The extension of aspartic acid racemization is higher in deep layers, so biopsy layer had a noteworthy influence.…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…The extent of this root translucency may be determined by computer mapping of serial hard tissue sections of the tooth. Regression tables prepared from large numbers of teeth of known age have been used to show that it is possible to determine the age of an unidentified body within about 7 years of the correct at death [24].…”
Section: Age Determination At Deathmentioning
confidence: 99%
“…It appears to take from 7 to 14 days before discoloration becomes apparent so this may give some gross indication of time of death [29].…”
Section: Time Elapsed Since Deathmentioning
confidence: 99%